2017
DOI: 10.1371/journal.pone.0177713
|View full text |Cite
|
Sign up to set email alerts
|

Serum HBV surface antigen positivity is associated with low prevalence of metabolic syndrome: A meta-analysis

Abstract: Background and aimAs there is conflicting evidence for the relationship between hepatitis B virus surface antigen (HBsAg) positivity and the prevalence of metabolic syndrome (MetS), we performed a meta-analysis to investigate whether HBsAg positivity affects the incidence of MetS.MethodsObservational studies on the relationship between HBsAg positivity and MetS were obtained from PubMed, Web of Science, and the Cochrane Library in April 2016. The pooled odds ratios (ORs) of MetS and its components (central obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 57 publications
(240 reference statements)
3
14
0
Order By: Relevance
“…A study using Korean National Health and Nutrition Examination Survey also showed an inverse association between HBsAg positivity and elevated triglycerides . A meta‐analysis of 14 cross‐sectional studies reported an inverse association between HBsAg positivity and elevated TGs with an odds ratio of 0.62 (95% CI, 0.59‐0.64), whereas HBsAg positivity was not associated with reduced HDL‐C in the same meta‐analysis of 13 studies . In the present large‐scale cohort study of apparently healthy individuals, we demonstrated a longitudinal association between HBsAg positivity and the development of dyslipidaemia over time.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…A study using Korean National Health and Nutrition Examination Survey also showed an inverse association between HBsAg positivity and elevated triglycerides . A meta‐analysis of 14 cross‐sectional studies reported an inverse association between HBsAg positivity and elevated TGs with an odds ratio of 0.62 (95% CI, 0.59‐0.64), whereas HBsAg positivity was not associated with reduced HDL‐C in the same meta‐analysis of 13 studies . In the present large‐scale cohort study of apparently healthy individuals, we demonstrated a longitudinal association between HBsAg positivity and the development of dyslipidaemia over time.…”
Section: Discussionsupporting
confidence: 69%
“…Several clinical studies have evaluated whether chronic viral infection is associated with dyslipidaemia, and have demonstrated an inverse association between HBV infection and lipid profiles . Furthermore, a meta‐analysis of 14 cross‐sectional studies reported an inverse relationship between HBsAg positivity and hypertriglyceridaemia . However, the cross‐sectional design of these studies limited their ability to establish a temporal relationship between HBV infection and reduced levels of lipid profiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 The most recently published review including 12 articles and a forest plot revealed an odds ratio of 0.8 for MetS prevalence in hepatitis B surface antigen-positive subjects compared to healthy controls. 46 Taken together, these lines of evidence imply that the risk of MetS is not increased in HBV patients. On the contrary, HBV infection may have a protective effect against MetS.…”
Section: Chroni C Hepatitis Vir Al Infec Tion and Me Tabolic Syndromementioning
confidence: 95%
“…A subgroup analysis suggested an inverse association in men and a sample population of under 45 years of age . The most recently published review including 12 articles and a forest plot revealed an odds ratio of 0.8 for MetS prevalence in hepatitis B surface antigen‐positive subjects compared to healthy controls …”
Section: Chronic Hepatitis Viral Infection and Metabolic Syndromementioning
confidence: 99%